SPIRIT Model: Character Building Strategies in the Society 5.0 Era through the Integration of Tazkiyatun Nafs and Spiritual Growth - Muhammad Asra; Muhammad Akbar (Universitas Pendidikan Ganesha, 2025)
Learning in the Society 5.0 era still tends to prioritize cognitive achievement, while the strengthening of students’ character and spirituality has not yet been optimally implemented in school practice. This situation creates a gap between the demand to develop character that is adaptive to digital challenges and the limited availability of systematic, practical instructional strategies for instilling spiritual and moral values. This study aimed to develop and validate the SPIRIT Model (Spiritual Personal Improvement and Reflective Integrated Teaching) as a character-strengthening strategy by integrating the concepts of Tazkiyatun Nafs and the Spiritual Growth Framework (SGF). The research employed a Research and Development (R&D) approach using the ADDIE model and involved 38 teachers, 50 students, and 24 Islamic Religious Education (PAI) teachers. Data were collected through questionnaires, interviews, and focus group discussions (FGDs). Three experts validated the model by assessing its content, presentation, syntax, and feasibility of implementation. The findings indicate that 95% of teachers reported a need for spirituality-based instructional strategies, and the SPIRIT Model—comprising five stages (Pre-Spiritual Awareness, Value Exploration, Spiritual Practice, Character Action, and Reflection & Feedback)—achieved an average score of 4.2, indicating a valid category. Therefore, the SPIRIT Model is theoretically and practically feasible as an innovative alternative for strengthening character education in the Society 5.0 era. The study provides a structured instructional syntax that can help teachers integrate spirituality-based character development into learning; however, further implementation trials are required to examine its effectiveness in producing comprehensive improvements in students’ character.